Effects of the lower jaw position on athletic performance of elite athletes. Issue 1 (4th December 2020) - Haughey, John Patrick; Fine, Peter
Abstract : When an athlete wears a mouthguard, the position of the lower jaw is changed by virtue of the teeth being unable to occlude. Little research is available in in this area, which have indicated both positive impact and no positive impact. Objectives: This study aims to explore the influence of the lower jaw position on athletic performance in elite athletes. Methods: A repeated measures study compared two lower jaw positions, the athlete's normal (habitual) bite and the lower jaw position when the muscles of mastication are at physiological rest (physiological rest bite). 15 athletes completed a medicine ball putt (upper body power), vertical jump (lower body power), sit and reach (composite hamstring flexibility), passive knee flexion (hamstring muscle length) and star excursion balance (stability and balance) tests in each condition. Results: Paired t-tests showed the physiological rest bite had significant (p<0.05) positive effect on athletic performance for each test. On average the physiological rest bite provided an increase of lower body power (5.8%), upper body power (10%), hamstring flexibility (14%) and balance and stability (4.8%) compared to the habitual bite. Conclusion: This study provides evidence of the need for further research to confirm if the lower jaw position can be optimised for athletic performance in athletes.